Phylogeny of Polycladida (Platyhelminthes) based on mtDNA data - Aguado Molina, María Teresa (2017)
A phylogenetic analysis of Polycladida based on two partial mitochondrial genes (cox1 and 16S) is provided. The analysis includes 30 polyclad terminals that represent species from the two taxa which traditionally divide the groups Cotylea and Acotylea. Our phylogenetic analyses produced a well-supported hypothesis that confirms the monophyly of Polycladida, as well as Acotylea and Cotylea. Within Acotylea, there are two lineages not highly supported: on one hand, Leptoplanoidea (excluding Hoploplana elisabelloi) and one Stylochoidea member (Pseudostylochus intermedius) (classification sensu Faubel, 1983, 1984), and on the other hand, Stylochoidea members together with Discocelis tigrina and H. elisabelloi. The genera Stylochus and Imogine are not monophyletic. Within Cotylea, Pseudocerotidae and Euryleptidae are monophyletic, though not highly supported, while Prosthiostomidae is not. Euryleptoidea is paraphyletic. The genera Pseudobiceros and Pseudoceros are monophyletic and highly supported. Our results suggest that, within Acotylea, the prostatoid organs of Discocelis may have been derived from a prostatic vesicle. The genus Hoploplana could be included in Stylochoidea. Within Cotylea, the common ancestor of Euryleptidae and Pseudocerotidae might have been an aposematic animal with tentacles.